Epidemiological Analysis of Major Complications Requiring Medical Intervention in Patients with Neurofibromatosis 1 - Yuichi Yoshida; Yuko Ehara; Monji Koga; Shinichi Imafuku; Osamu Yamamoto (Medical Journals Sweden, 2018)
Neurofibromatosis 1 has various complications. To elucidate the frequency of neurofibromatosis 1-related major complications requiring medical intervention, a nationwide retrospective study was conducted of 3,530 patients with neurofibromatosis 1 registered from 2001 to 2014 in Japan. The ratio of certified patients requiring medical intervention (>stage 3) was 82%. Patients classified in the most severe grade experienced dermatological complications (71.8% of patients), neurological complications (38.1%) and bone complications (33.3%). In patients with dermatological manifestations, medical treatment was needed for cutaneous neurofibromas (58%), diffuse plexiform neurofibromas (31%) and malignant peripheral nerve sheath tumours (10%). Patients with neurological manifestations needed medical treatment mainly for brain tumours (53%) and intellectual disability (26%). Patients with bone manifestations needed medical treatment for pseudoarthrosis (9%), scoliosis (55%) and bone defects (16%). It is necessary for physicians to be aware of neurofibromatosis 1-related complications requiring medical intervention in order to provide appropriate care for patients with neurofibromatosis 1.